(untitled) (Journal of Comparative & International Higher Education, 2024)
Acculturative stress may hamper international students’ ability to succeed in the United States of America. This study analyzed the impact of a range of factors noted in the literature and compared the levels of stress they were related to before and during the COVID-19 pandemic. We collected three waves of data (total responses = 204) via an online survey from ten universities/colleges across different regions in the United States of America. The results indicated that English proficiency and sex predicted the overall acculturative stress of Asian international students, in which higher perceived English proficiency predicted a lower perceived acculturative stress, and female Asian international students experienced higher acculturative stress than males. Also, Asian international students are experiencing more sadness during the pandemic and their peers are more discriminated against during 2020. Thus, university administrators should promote English language programs and support services (e.g., gender specific student support) to effectively address Asian students’ concerns.